Ce doped NiO nanoparticles as selective NO2 gas sensor. (March 2018) - Gawali, Swati R.; Patil, Vithoba L.; Deonikar, Virendrakumar G.; Patil, Santosh S.; Patil, Deepak R.; Patil, Pramod S.; Pant, Jayashree
Abstract: Metal oxide gas sensors are promising portable gas detection devices because of their advantages such as low cost, easy production and compact size. The performance of such sensors is strongly dependent on material properties such as morphology, structure and doping. In the present study, we report the effect of cerium (Ce) doping on nickel oxide (NiO) nano-structured thin film sensors towards various gases. Bare NiO and Ce doped NiO nanoparticles (Ce:NiO) were synthesized by sol-gel method. To understand the effect of Ce doping in nickel oxide, various molar percentages of Ce with respect to nickel were incorporated. The structure, phase, morphology and band-gap energy of as-synthesized nanoparticles were studied by XRD, SEM, EDAX and UV–vis spectroscopy. Thin film gas sensors of all the samples were prepared and subjected to various gases such as LPG, NH3, CH3 COCH3 and NO2 . A systematic and comparative study reveals an enhanced gas sensing performance of Ce:NiO sensors towards NO2 gas. The maximum sensitivity for NO2 gas is around 0.719% per ppm at moderate operating temperature of 150 °C for 0.5% Ce:NiO thin film gas sensor. The enhanced gas sensing performance for Ce:NiO is attributed to the distortion of crystal lattice caused by doping of Ce into NiO. Graphical abstract: The effect of cerium doping on nickel oxide (CNO) nano-structured thin film sensors towards various gases such as LPG, NH3, CH3 COCH3 and NO2 is investigated. An enhanced gas sensing performance towards NO2 gas is revealed with a maximum sensitivity of 0.72% per ppm at moderate operating temperature of 150 °C for 0.5% CNO sensor. This is attributed to the distortion of crystal lattice caused by doping of Ce into NiO nano-structures. Highlights: The Ce doped NiO exhibited excellent and highly selective gas response for NO2 gas at relatively low temperature i.e. 150 °C. The synthesis route and sensing behavior of as synthesized Ce doped NiO revealed a promising candidate for fabricating low-consumption gas sensors.